THE IMPLEMENTATION OF LILIFUK CUSTOMARY LAW TOWARDS COASTAL ENVIRONMENTAL DEGRADATION OF KUPANG BAY - Ranny Christine Unbanunaek; Jimmy Pello (Faculty of Law, Universitas Jenderal Soedirman, 2016)
The kuanheun coastal communities have a customary law that help maintain coastal environmental sustainability resourceS called as lilifuk customary law(lilifuk atolan instrument). This research applied empirical method by formulating three problems: what are the values embedded in lilifuk customary law; how is the of lilifuk customary law contribution to prevent coastal environmental degradation; and how is the correlation between lilifuk customary law values and the law provision on coastal areas and small islands management.The result of the research identified the following; the first, Lilifuk customary law contains religious value, ecological value, communal value, social relations value, solidarity and responsibility value, social leadership value, and educational value. Second, the settlement of law violation by lilifuk customary law is conduted by the following steps: reporting; discussion; verdict; and execution. Third, there is a correlation between the lilifuk customary lilifuk values and WP3K Law values.Keywords: lilifuk customary law, environmental degradation, kupang bay